Circulating CXCR5-Expressing CD8+ T Cells Are Major Producers of IL-21 and Associate With Limited HIV Replication (2018)
ABSTRACT: Background: Despite advances made with the highly active antiretroviral therapy (HAART) in the control of the HIV 1 infection, a cure has not been achieved because of the persistence of viral reservoirs. The major HIV reservoirs remain in the lymphoid follicles because of, among other factors, the partial absence of CD8+ T-cells in these structures. Recently, lymphoid follicle– confined and circulating CD8+ T-cells expressing the C-X-C chemokine receptor type 5 (CXCR5) were described, possessing antiviral mechanisms that could help to control HIV replication. Setting and Methods: By flow cytometry, we characterized the phenotype and function of circulating CXCR5-expressing CD8+ Tcells in HIV-infected patients with natural or HAART-induced control of HIV replication. Results: Circulating CXCR5-expressing CD8+ T-cells exhibited low or null expression of the C–C chemokine receptor type 7 (CCR7) and had a transitional memory phenotype. Particular redistributions of CXCR5-expressing CD8+ T-cells were found in HIV-infected patients, and they were partially restored by HAART. The frequency of CXCR5hiCCR72/lo CD8+ T-cells was higher in spontaneous HIV controllers and negatively correlated with plasma HIV RNA levels. Total and HIV-specific CXCR5+ CD8+ T-cells were major producers of interleukin-21, and this function was positively associated with their interferon-g production. Conclusions: Circulating CXCR5-expressing CD8+ T-cells are associated with low-level HIV replication; these cells could be novel correlates of protection, and potentially useful in the eradication of HIV reservoirs.